Presentation Of Indonesian Language Teaching Materials - Diah Kusyani (Yayasan Insan Cipta Medan, 2023)
Learning materials need to be selected and presented appropriately so that learning objectives are achieved optimally. There are several criteria that need to be considered in selecting and presenting teaching materials. Some of these criteria are the principles of selecting teaching materials, the stages of selecting teaching materials, and the criteria for presenting teaching materials. The principles of selecting teaching materials include the principle of relevance, the principle of adequacy, and the principle of consistency. The stages of selecting teaching materials include determining the behavioral aspects contained in competency standards and basic competencies, as well as determining or selecting the types of teaching materials that are in accordance with the behavioral aspects contained in competency standards and basic competencies. Meanwhile, the criteria for presenting teaching materials include the inclusion of learning objectives, the stages of learning (sequencing of teaching materials), attracting the interest and attention of students, involving the activeness of students, the relationship between teaching materials, questions, and norms for presenting teaching materials. With regard to the selection and presentation of teaching materials for Indonesian Language and Literature subjects, apart from the need to consider the criteria above, other criteria must also be considered, namely: scientific criteria for Indonesian language and literature, criteria for education and teacher training, and criteria for readability of teaching materials.